2003
DOI: 10.1111/j.1752-0606.2003.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interpersonal Fusion: Reliability and Validity of a New Dsi Fusion With Others Subscale

Abstract: The Differentiation of Self Inventory (DSI) is a multidimensional measure of differentiation consisting of four subscales focusing on adults (ages 25+), and their significant relationships, including current relationships with family of origin. Although the DSI full scale and three of its subscales are theoretically and psychometrically sound, the Fusion with Others (FO) subscale is lacking. Therefore, responses of 225 adults were used to revise the FO subscale. Results yielded a 12-item, revised FO subscale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
399
1
27

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(448 citation statements)
references
References 25 publications
21
399
1
27
Order By: Relevance
“…The Differentiation of Self Inventory (Skowron & Schmitt, 2003) is a 46-item, self-report measure of differentiation of self in adulthood and is grounded in BFST (Bowen, 1978;Kerr & Bowen, 1988). The four subscales of the DSI-R are as follows.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Differentiation of Self Inventory (Skowron & Schmitt, 2003) is a 46-item, self-report measure of differentiation of self in adulthood and is grounded in BFST (Bowen, 1978;Kerr & Bowen, 1988). The four subscales of the DSI-R are as follows.…”
Section: Instrumentsmentioning
confidence: 99%
“…Originally comprising 43 items, it underwent revisions (Skowron & Schmitt, 2003) to strengthen its subscale, Fusion with Others, which resulted in a 46-item revised DSI.The DSI is arguably the most recognised and widely used measure of differentiation of self from a BFST perspective (Licht & Chabot, 2006;. A search of PsyInfo from the period of 1980 to 2010, showed that approximately half of the published research on differentiation relies on it to operationalize the construct .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, internal consistency for the full-scale was found to strong with a Cronbach's alpha of .87. Skowron and Schmitt (2003) found that internal consistency was moderately strong, ranging from .81 to .89, and that full scale consistency was strong with a Cronbach's alpha of .92. Construct validity is indicated by relationship found between DSI scores and less symptomatology as well as less chronic anxiety (Skowron & Friedlander, 1998).…”
Section: Differentiation Of Selfmentioning
confidence: 99%
“…Para além disso, fez-se uma análise de clusters no grupo de jogadores patológicos. Adicionalmente aos instrumentos referidos no Estudo 1, utilizaram-se os seguintes: Escala de Avaliação da Satisfação em Áreas da Vida Conjugal (EASAVIC) (Narciso & Costa, 1996), Escala de Congruência (CS) (Lee, 2002b;versão portuguesa de Cunha, Silva, & Relvas, 2014), Inventário de Diferenciação do Self -Revisto (DSI-R) (Skowron & Schmitt, 2003;versão portuguesa de Major, Rodríguez-González, Miranda, Rousselot, & Relvas, 2014) e seis questões independentes que avaliam os aspetos transgeracionais e relativos ao contexto social (aceitação e acessibilidade) supramencionados. Os resultados indicam que, embora os dois grupos de jogadores não patológicos apresentem diferentes níveis de gravidade quanto ao seu jogo, não se diferenciam estatisticamente um do outro, sugerindo que os problemas relacionados com o jogo apenas são evidentes quando se atinge o nível patológico.…”
Section: Introductionunclassified